Micro-organisms in outpatient infantile gastroenteritis. Issue 3 (March 1980) - Weindling, A M; Walker-Smith, J A; Bird, R
Abstract : This study reports the results of an examination of the stools of 58 infants with gastroenteritis who were seen as outpatients. The stools were examined by routine bacterial culture, and by electron microscopy for virus particles. The stools of a comparable control group of infants who had no gastrointestinal symptoms were also similarly examined. Enteropathogenic Escherichia coli, Salmonella sp., and rotaviruses, as well as other viruses, particularly adenoviruses and coronaviruses, were isolated.